Ectoparasitic mites on Hemidactylus mabouia lizards (Squamata: Gekkonidae) - Otavio Silva, Eduardo (2023)
This work aimed to determine mite species in H. mabouia lizards in Arapiraca region, as well as to verify if the mites present in the lizards are shared with native species, such as members of the genus Tropidurus. The collection of H. mabouia took place from February to May 2019, using traps and nets. The lizards were captured alive in the Pé Leve Velho village, Arapiraca – AL, then sent to the Laboratory of Entomology and Acarology at UFAL Campus de Arapiraca so that a detailed examination of the epidermis region could be carried out using a stereomicroscope to detect ectoparasites. Ten specimens of H. mabouia were captured. A total of 348 ectoparasitic mites were found in them. The occurrence of mites of the Pterygosomatidae families, genus Geckobia was also verified in all captured lizards. The mean intensity of infestation was 34.8 mites per lizard. There was no record of ectoparasite mites in Tropidurus lizards.